Meeting the emotional needs of hospital patients with dementia: a freelisting study with ward staff - Petty, Stephanie; Dening, Tom; Griffiths, Amanda; Coleston, Donna Maria (Oxford University Press, 2018)
Background and Objectives: People with dementia are vulnerable when in hospital, with serious risks to their physical and emotional wellbeing. Hospital staff are expected to understand and respond to the emotions of the patient; however, it is not known how this can be achieved. We provide a concise description of achievable emotion-focused care for patients with dementia. Design and Methods: Exploratory qualitative interviews were conducted with a whole UK hospital ward providing dementia care, constituting 47 staff members. Staff responded to four questions using ethnographic freelisting. They listed: (1) all the ways they notice the emotional distress of patients with dementia, (2) the causes of emotional distress, (3) all the ways they respond and (4) the responses that seem to work. Cultural consensus analysis was applied. Results: A single-factor solution for each question indicated a consensus approach to emotional distress. Emotional distress was noticed from agitation (Smith’s saliency score, 0.418), crying (0.350) and increased mobilising (0.238). The main causes of distress were the unfamiliar hospital environment (0.355) and not knowing what is happening (0.313). The most effective ways to respond to emotional distress required knowing the person (0.299), talking (0.283) and being with the person (0.269). Discussion and Implications: The findings expand what is understood of behavioural and psychological symptoms of dementia; these communicated emotional distress with well-understood causes. Prioritised ways of responding to emotional distress described person-centred care. The results offer a menu of options for providing emotionally-responsive care for patients with dementia in hospital. Future research should evaluate the care described.